Pharmacokinetics and disposition of dalcetrapib in rats and monkeys. (December 2014) - Takubo, Hiroaki; Ishikawa, Tomohiro; Kuhlmann, Olaf; Nemoto, Hiroyuki; Noguchi, Tomoyuki; Nanayama, Toyomichi; Komura, Hiroshi; Kogayu, Motohiro
Abstract 1. The pharmacokinetics and metabolism of dalcetrapib (JTT-705/RO4607381), a novel cholesteryl ester transfer protein inhibitor, were investigated in rats and monkeys. 2. In in vitro stability studies, dalcetrapib was extremely unstable in plasma, liver S9 and small intestinal mucosa, and the pharmacologically active form (dalcetrapib thiol) was detected as major component. Most of the active form in plasma was covalently bound to plasma proteins via mixed disulfide bond formation. 3. Following oral administration of 14C-dalcetrapib to rats and monkeys, active form was detected in plasma. The active form was mainly metabolized to the glucuronide conjugate and the methyl conjugate at the thiol group. Several minor metabolites including mono- and di-oxidized forms of the glucuronide are also detected in the plasma and urine. 4. The administered radioactivity was widely distributed to all tissues and mainly excreted into the feces (85.7 and 62.7% of the dose in rats and monkeys, respectively). Most of the radioactivity was recovered by 168 h. Although the absorbed dalcetrapib was hydrolyzed to the active form and was bound to endogenous thiol via formation of disulfide bond, it was relatively rapidly eliminated from the body and was not retained.